Jurgis Baltrusaitis’ Letters to Giovanni Papini - Keturakis, Ugnius (Respectus Philologicus, 2017)
The promethean program of Jurgis Baltrušaitis’ creation is especially distinctly expressed in the poet’s letters to Giovanni Papini. The world here is divided into two spheres – the earthly and the divine, and the mission of the creator is to connect them. The letters also demonstrate the motives of promethean worldview which are not so obvious in J. Baltrušaitis’ poetry: the motive of a poet-prophet, clairvoyant; self-creation of a human-creator, development into a divine, perfect individuality that can re-build the world; pursuit of absolute creativity as complete freedom of the creator; faith in the human ability to build a tower that reaches the sky – revival of the myth of tower of Babel; defiance of idealistic attitude and earthliness and pursuit of divinity; exaltation of seeing, vision as the only connection with the world of ideas. J. Baltrušaitis’ and G. Papini’s correspondence allows relating J. Baltrušaitis’ creative work not only with the Russian but also with the European tradition of symbolism. The correspondence of the two promethean minded poets – prophets was interrupted by World War I which also ruined the mythologem as a belief in the possibility of changing the world, and by the October Revolution, following the war.